2021
DOI: 10.1038/s41598-021-92474-8
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA FER1L4 is dysregulated in osteoarthritis and regulates IL-6 expression in human chondrocyte cells

Abstract: Osteoarthritis (OA) is the most prevalent joint disease and is one of the major causes of disability in the world. There has been an increase in the incidence of OA, which is associated with an aging population, sedentary lifestyle, and reduced physical activity. Due to the complex OA pathogenesis, there are limited diagnostic tools. OA is a degenerative joint disorder with a recognized inflammatory component, usually described as abnormal expression of inflammatory factors. For instance, interleukin 6 (IL‐6) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…in cartilage, synovium and subchondral bone [ 25 ]. FER1L4 regulates inflammatory factor IL-6 in osteoarthritis-affected cartilage [ 26 ] and is linked to VEGF, an osteoarthritis-linked angiogenic factor [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…in cartilage, synovium and subchondral bone [ 25 ]. FER1L4 regulates inflammatory factor IL-6 in osteoarthritis-affected cartilage [ 26 ] and is linked to VEGF, an osteoarthritis-linked angiogenic factor [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…OA-modifying drugs have been developed to relieve pain and suppress inflammation. Furthermore, micro RNA (miRNA), as well as long noncoding RNA (lncRNA), can also be employed as cargo to transport into OA joints for modulating the inflammation state [ [191] , [192] , [193] ]. However, systemic administration or local joint injection may give rise to problems, such as low drug efficacy and overly rapid clearance rates [ 194 , 195 ].…”
Section: Articular Cartilage Regeneration Under Abnormal Conditionsmentioning
confidence: 99%
“…Previous studies have shown that there is a relationship between the blood level of lncRNAs and OA progression ( Table 2 ). For instance, lncRNA DILC ( 145 ), and lncRNA FER1L4 ( 146 ) were also found to be closely associated with OA inflammatory condition in plasma. As ANCR is known to regulate TGF-β signaling, Li and colleagues proposed that the plasma levels of TGF-β1 and ANCR could differentiate OA patients from healthy control subjects.…”
Section: Clinical Biomarkers Of Lncrnas For Oa Diagnosismentioning
confidence: 99%